Duplicated appendix with an acute abdomen in 16 years old female with both appendices inflamed: a rare case report - S., Shivakumar; Kumar, Uday (International Surgery Journal, 2020)
Duplicated appendix is a rare congenital anomaly with incidence of 0.004-0.009% and its mostly an incidental finding on table, when one of them is acutely inflamed and very rarely both of them can be inflamed as in this case. Report a case of young girl who presented with complain of pain abdomen and vomiting in the last 2 days. Clinically patient was diagnosed to have acute appendicitis and on laparoscopy, patient had duplicated appendix one at the ileocaecal valve and the other 2cm away near the caecum with pus and faecolith. Histopathology confirmed appendicitis in the both appendices. Reported about this interesting rare case because even though the incidence of duplicated appendix is too low (0.004-0.009%), should always search for the missed appendix in patients who underwent appendicectomy earlier and complains of severe pain in right iliac fossa. Aim was to report such a rare interesting case and give a small gentle reminder to the surgeons as duplicated appendix even though rare but still a possibility.